2009
DOI: 10.1097/aud.0b013e3181a61bf2
|View full text |Cite
|
Sign up to set email alerts
|

Preattentive Cortical-Evoked Responses to Pure Tones, Harmonic Tones, and Speech: Influence of Music Training

Abstract: Objective: Cortical auditory evoked potentials, including mismatch negativity (MMN) and P3a to pure tones, harmonic complexes, and speech syllables, were examined across groups of trained musicians and nonmusicians. Because of the extensive formal and informal auditory training received by musicians throughout their lifespan, it was predicted that these electrophysiological indicators of preattentive pitch discrimination and involuntary attention change would distinguish musicians from nonmusicians and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
54
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 75 publications
7
54
3
4
Order By: Relevance
“…In the literature, there are studies reporting latency differences (9,3,17). Musacchia et al (3) found P1 and N1 peaks earlier in the musician group.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies reporting latency differences (9,3,17). Musacchia et al (3) found P1 and N1 peaks earlier in the musician group.…”
Section: Discussionmentioning
confidence: 99%
“…In rhythmically trained musicians, P3b latencies were shorter for irregular sound omissions in rhythmic contexts (Jongsma, Desain, & Honing, 2004). Similarly, P3a latencies for pitch deviant sounds were shorter when musically trained participants were asked to ignore sounds (Nikjeh et al, 2009). These findings indicate stronger, faster involuntary attention switching (P3a) and enhanced matching of the working memory trace (P3b) to relevant target sounds in musicians.…”
mentioning
confidence: 91%
“…Sounds were presented in an oddball paradigm in which infrequently presented deviant target sounds were interspersed among frequently presented standard sounds. On the basis of previous studies of P3a and P3b potentials in musicians (Nikjeh et al, 2009;Tervaniemi et al, 2005;Vuust et al, 2009), we hypothesized that auditory perceptual learning, as indicated by rapid plasticity changes of the P3a/P3b for deviating target sounds during a single experimental session, would differ between musicians and nonmusicians. In some studies, music training enhanced only P3b responses during attentive discrimination tasks, and not P3a responses to unattended sounds (Besson & Faïta, 1995;Tervaniemi et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The objective measurement of central auditory processing and integrity of final auditory pathway should not depend on just one component but on the presence of several ERPs (complex), reflecting progressive central sound processing and representation Näätänen et al 2007;Nikjeh et al 2009) and also preservation of neuronal synchrony encoding temporal information (Rance et al 2002;Tomé et al 2012). …”
mentioning
confidence: 99%